P619 Patterns of Anti-TNF Prescribing & Therapy Outcome in a Large Multicentre Cohort of Inflammatory Bowel Disease Patients. (21st January 2022) - Doherty, J; Stack, R; O Morain, N; Coe, C; Corcoran, R; Ryan, B; Doherty, G; Mc Namara, D; Kevans, D
Abstract: Background: Anti-TNF agents are effective therapies for Inflammatory Bowel Disease (IBD), however, a significant proportion of patients lose response over time. Real world data on prescribing practices and outcome of anti-TNF therapy are of utility to practicing clinicians Methods: To evaluate Anti-TNF prescribing practice and durability of Anti-TNF response in a large multicentre IBD cohort. IBD patients commencing an anti-TNF agent, as first biologic therapy, at participating academic centres were identified from institutional databases. Baseline demographic data, concomitant medication and biologic therapy history were collected. Adalimumab(ADA) and Golimumab(GOL) were consider subcutaneous(SC) anti-TNF agents. Date of commencement and discontinuation of first and second line anti-TNF therapy was documented. Kaplan-Meier survival curves were constructed for time based analyses. P values less than 0.05 were considered significant in all analyses. Results: N=991 patients with IBD were included in the study. 29%, 69% and 2% had UC, CD and IBD-U respectively; median [IQR] age 27 [19–37] years; 50% female. 31%, 63% and 4% received infliximab(IFX), ADA and GOL respectively as first-line anti-TNF therapy. 35% of patients received an immunomodulator in combination with first-line anti-TNF agent. Median [95% CI] survival free of therapy discontinuation for first and second-line anti-TNF agents was 4.6 [3.7 – 5.3] years and 3.0 [2.1 – 3.9] years respectively. Survival free of anti-TNF discontinuation was significantly shorter for IFX monotherapy group compared with IFX combination therapy, SC anti-TNF monotherapy and SC anti-TNF combination therapy groups, p=0.005. Conclusion: While anti-TNF therapies are effective a significant proportion of patients discontinue therapy over time. Second line anti-TNF therapy results in a less durable response with a shorter time to drug discontinuation compared with first line anti-TNF therapy. The use of a combination immunomodulator is particularly important with infliximab therapy, however, does not influence durability of response for subcutaneous anti-TNF agents.